2010
DOI: 10.1146/annurev-soc-070308-120011
|View full text |Cite
|
Sign up to set email alerts
|

Social Relationships and Health Behavior Across the Life Course

Abstract: Sociological theory and research point to the importance of social relationships in affecting health behavior. This work tends to focus on specific stages of the life course, with a division between research on childhood/adolescent and adult populations. Yet recent advances demonstrate that early life course experiences shape health outcomes well into adulthood. We synthesize disparate bodies of research on social ties and health behavior throughout the life course, with attention to explaining how various soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
817
2
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 986 publications
(889 citation statements)
references
References 131 publications
(172 reference statements)
31
817
2
11
Order By: Relevance
“…A associação encontrada entre apoio de interação social positiva e IMC era esperada, já que pressupõe a existência de vínculos sociais que proporcionam estímulo para atividades que beneficiam a saúde e a estética. A abordagem comportamental preconiza que os contatos sociais exercem influência e regulação sobre o indivíduo, incentivando a modificação dos hábitos pelo aumento do senso de responsabilidade, contribuindo para a saúde ao estimular comportamentos que a promovam em detrimento daqueles que a comprometem 8,32,33 . Assim, a associação negativa encontrada entre essa dimensão e o IMC, especificamente entre os homens de 40-49 anos, pode estar relacionada com preocupações sobre a imagem corporal, em que estudos sugerem o aumento da prática de comportamentos saudáveis por meio dos contatos sociais, como a redução do consumo de álcool, o abandono do hábito de fumar e adesão à prática de atividades físicas 13,27,34 .…”
Section: Tabelaunclassified
“…A associação encontrada entre apoio de interação social positiva e IMC era esperada, já que pressupõe a existência de vínculos sociais que proporcionam estímulo para atividades que beneficiam a saúde e a estética. A abordagem comportamental preconiza que os contatos sociais exercem influência e regulação sobre o indivíduo, incentivando a modificação dos hábitos pelo aumento do senso de responsabilidade, contribuindo para a saúde ao estimular comportamentos que a promovam em detrimento daqueles que a comprometem 8,32,33 . Assim, a associação negativa encontrada entre essa dimensão e o IMC, especificamente entre os homens de 40-49 anos, pode estar relacionada com preocupações sobre a imagem corporal, em que estudos sugerem o aumento da prática de comportamentos saudáveis por meio dos contatos sociais, como a redução do consumo de álcool, o abandono do hábito de fumar e adesão à prática de atividades físicas 13,27,34 .…”
Section: Tabelaunclassified
“…With regard to the family sphere, it was shown that the family environment not only shapes the life course of individuals but also deeply influences their wellbeing (Uhlenberg and Mueller 2003). Recent research examining the increasing diversity in family structures emphasizes that parenthood and parenting experiences influence wellbeing over life (Umberson et al 2010). Growing evidence suggests that the accumulation of social roles affects both men's and women's health (Bartley et al 1999;Bianchi and Milkie 2010).…”
Section: The Added Value Of the Life Course Perspective To The Analysmentioning
confidence: 99%
“…The interaction between parents (as proximal social determinants of health) and adolescents, and parents’ subjective norms/values and their action on the growth characteristics of adolescents can positively/negatively influence their general health and well-being (Blum et al, 2012; Lindqvist, Kostenius, Gard, & Rutberg, 2015; Sawyer et al, 2012; Viner et al, 2012; Umberson, Crosnoe, & Reczek, 2010). In fact, from some parents, the most common criticisms are related to the adolescent’s physical appearance or body size and they make every effort to adjust it.…”
Section: Introductionmentioning
confidence: 99%